2013
DOI: 10.1016/j.jneumeth.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative fluorescence microscopy provides high resolution imaging of passive diffusion and P-gp mediated efflux at the in vivo blood–brain barrier

Abstract: Quantitative fluorescent microscopy is an emerging technology that has provided significant insight into cellular dye accumulation, organelle function, and tissue physiology. However, historically dyes have only been used to qualitatively or semi-quantitatively (fold change) determine changes in blood–brain barrier (BBB) integrity. Herein, we present a novel method to calculate the blood to brain transfer rates of the dyes rhodamine 123 and Texas red across the in situ BBB. We observed that rhodamine 123 is su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Rhodamine 123 is subject to P-gp mediated efflux at both the BBB and the BTB. When rhodamine 123 and an inhibitor of P-gp are administered concurrently, dye accumulates in brain ~10- to 12-fold higher than in the absence of efflux inhibition [34]. Similarly, in this work, when Verapamil or Cyclosporine A was added to the outer chamber of the microfluidic device, Rhodamine 123 accumulation increased similar to in vivo reports [9].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Rhodamine 123 is subject to P-gp mediated efflux at both the BBB and the BTB. When rhodamine 123 and an inhibitor of P-gp are administered concurrently, dye accumulates in brain ~10- to 12-fold higher than in the absence of efflux inhibition [34]. Similarly, in this work, when Verapamil or Cyclosporine A was added to the outer chamber of the microfluidic device, Rhodamine 123 accumulation increased similar to in vivo reports [9].…”
Section: Discussionsupporting
confidence: 81%
“…1) in a novel microfluidic BBB and BTB model as validation to previously published literature [34]. Briefly in this model, endothelial cells are seeded in the outer compartments, while astrocytes (BBB) or brain seeding breast cancer cells (BTB) are seeded in the central compartment.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Rhodamine-123 (MW = 380,8 g/ mol, LogP = 1.0 [76]) is a fluorescent ABCB1 substrate dye. Using in situ brain perfusion, it was shown that diffusion of rhodamine-123 across the BBB was increased up to 20-fold by ABCB1 inhibition in rats [77]. This showed the ability of Rhodamine-123 to cross the physical BBB and a predominant impact of ABCB1 in restricting the BBB permeation of this compound [76].…”
Section: Discussionmentioning
confidence: 95%